PELATIHAN DESAIN GRAFIS YANG KREATIF UNTUK SISWA SEKOLAH DASAR - Aryan Nusi; Yasin Kumai (Journal of Community Services on Multidisciplinary Sciences, 2025)
This Canva-based graphic design training aims to enhance visual literacy and digital skills among elementary students in Tilongkabila District. Using a hands- on and engaging approach, students were introduced to basic design elements such as color, layout, and typography. The five-day program involved demonstrations, practice, discussions, and evaluations. The results showed that students were able to create digital posters independently, understand basic design principles, and exhibit increased creativity and confidence in expressing ideas through visual media